Dependence of thermal diffusivity on particle size in Au nano-fluid - Zamiri, Reza; Zakaria, Azmi; Shahriari, Esmaeil; Mat Yunus, Wan Mahmood; Naghavi, Kazem; Saion, Elias; Mahdi, Mohd Adzir; Husin, Mohd Shahril (National Institute of Research and Development for Optoelectronics, 2010)
In this paper we report the measurement of thermal diffusivity of gold nanofluid prepared by γ-radiation with various particle sizes ranging from 7.0 nm to 18.7 nm. The thermal lens technique is used to measure thermal diffusivity of gold nano-fluid. In this technique a diode laser (wavelength 514 nm, power 80 mW) and He-Ne laser were used as the excitation source and probe beam respectively. Experimental results showed that thermal diffusivity values of nanofluid increase when the particle size increase.